INTEGRATION OF CIVIC EDUCATION, PANCASILA EDUCATION, AND VALUES EDUCATION IN SHAPING STUDENTS’ CIVIC RESPONSIBILITY IN THE DIGITAL ERA: A MIXED METHODS APPROACH - H. Bambang Yuniarto (International Journal of Teaching and Learning, 2025)
The digital era presents significant challenges for students as the younger generation in fostering civic responsibility, particularly amid the proliferation of disinformation, low levels of digital literacy, and growing political apathy. This study aims to analyze the integration of Civic Education, Pancasila Education, and Values Education in shaping students’ civic responsibility at the higher education level. Employing a mixed methods approach with an explanatory sequential design, the research combines quantitative surveys of students with in-depth interviews, observations, and document analysis as qualitative data. The findings reveal that students perceive the integration of these three courses to be at a high level, especially in the dimensions of academic compliance, organizational participation, digital literacy, and ethical engagement on social media. Qualitative results further emphasize that values of democracy, morality, and social concern are internalized by students in both academic practices and digital interactions, although challenges remain in the form of negative influences from social media and the currents of globalization. The study contributes theoretically by expanding the concept of civic responsibility through the integration of digital citizenship dimensions and provides practical implications for curriculum development and teaching methods that are adaptive to the digital era. These findings highlight the importance of synergy between educational institutions, educators, and students in strengthening the role of civic education in the society 5.0 era.